Heavy metal a tank company's battle to Baghdad - Conroy, Jason; Martz, Ron (AUSA Institute of Land Warfare book, 2005)
Through the personal stories of the young troopers of Charlie Company - who experienced a very different war from what was seen back home on TV - Heavy Metal tells us much about the qualities of today's American soldier, about twenty-first-century desert and urban warfare, and about how the Army should prepare to fight.